2018
DOI: 10.1007/s00520-018-4061-0
|View full text |Cite
|
Sign up to set email alerts
|

Content validity and electronic PRO (ePRO) usability of the Lung Cancer Symptom Scale-Mesothelioma (LCSS-Meso) in mesothelioma patients

Abstract: Results support the content validity of the LCSS-Meso and the usability of the electronic format for use in assessing symptoms among patients with pleural mesothelioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Fatigue is common, with up to 86% of participants in the intervention arm of our study reporting such (from the SPARC tool), and at least 27% reporting "tiredness" in the overall cohort (from the QLQ-C30). This is consistent with other studies, reporting rates between 61-94% 2,29 . Fatigue is a difficult symptom to manage and is perhaps related to pro-inflammatory cytokines which are themselves related to the neutrophil-lymphocyteratio and vascular endothelial growth factor 16 .…”
Section: Independence and Support/familysupporting
confidence: 94%
See 1 more Smart Citation
“…Fatigue is common, with up to 86% of participants in the intervention arm of our study reporting such (from the SPARC tool), and at least 27% reporting "tiredness" in the overall cohort (from the QLQ-C30). This is consistent with other studies, reporting rates between 61-94% 2,29 . Fatigue is a difficult symptom to manage and is perhaps related to pro-inflammatory cytokines which are themselves related to the neutrophil-lymphocyteratio and vascular endothelial growth factor 16 .…”
Section: Independence and Support/familysupporting
confidence: 94%
“…Fatigue was also a prominent physical symptom in our study, in common with other reports 28,29 . It is a key physical symptom predictive of survival and an established unmet need within the cancer population 9,17 .…”
Section: Independence and Support/familysupporting
confidence: 92%
“…The MDASI-MPM was developed according to the general principles expressed in the FDA’s guidance on the use of PROs in labeling claims [4], including qualitative generation of items. While none of the HRQOL measures validated for use in patients with MPM were developed with qualitative input from patients with MPM, a recent paper [5] evaluated the content validity of the LCSS-Meso in qualitative interviews with patients with MPM, although an expert panel evaluation of the relevance of these symptoms was not done. This study found that the symptoms reported by 20% or more of the 18 patients with MPM interviewed were shortness of breath, fluid build-up, coughing, fatigue, pain, weight loss, and appetite changes.…”
Section: Discussionmentioning
confidence: 99%
“…The LCSS-Meso is a valid and reliable QOL measure that was designed for patients with non-small cell lung cancer and that has been modified for use in patients with MPM. A recent paper [5] presents cognitive debriefing of the LCSS-Mesothelioma. One of the 8 items in the LCSS-Meso is a global QOL rating (rated using a visual analogue scale on a 0–100 scale).…”
Section: Methodsmentioning
confidence: 99%
“…Patients managing chronic conditions have reported satisfaction in web-based reporting systems that facilitate effective communication of biomedical metrics (eg, blood pressure and weight) [ 11 ]. Recent studies have demonstrated the usability and implementation of HIT platforms to collect electronic patient-reported outcomes (ePROs), such as biomedical metrics for disease management [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%